Assessment of the effects of corporate governance codes on corruption in Tanzania’s public sectors - Bajwalah, Asha Juma (Mzumbe University, 2024)
A Dissertation submitted in partial fulfillment of the requirements for the award of Master of Science in Accounting and Finance (MSc – A & F) of Mzumbe University